Delivery of Formulated Industrial Enzymes with Acoustic Technology. (February 2016) - Hwang, Jennifer Dorcas; Ortiz-Maldonado, Mariliz; Paramonov, Sergey
Industrial enzymes are instrumental in many applications, including carbohydrate processing, fabric and household care, biofuels, food, and animal nutrition, among others. Enzymes have to be active and stable not only in harsh application conditions, but also during shipment and storage. In protein stability studies, formulated concentrated enzyme solutions are frequently diluted gravimetrically prior to enzyme activity measurements, making it challenging to move toward more high-throughput techniques using conventional robotic equipment. Current assay methods pose difficulties when measuring highly concentrated proteins. For example, plastic pipette tips can introduce error because proteins adsorb to the tip surface, despite the presence of detergents, decreasing precision and overall efficiency of protein activity assays. Acoustic liquid handling technology, frequently used for various dilute small-molecule assays, may overcome such problems. Originally shown to effectively deliver dilute solutions of small molecules, this technology is used here as an effective alternative to the aforementioned challenge with viscous concentrated protein solutions. Because the acoustic liquid handler transfers nanoliter quantities of liquids without using pipette tips and without sample loss, it rapidly and uniformly prepares assay plates for enzyme activity measurements within minutes. This increased efficiency transforms the nature of enzyme stability studies toward high precision and throughput.